Reação de transesterificação de óleo de mamona utilizando TiO2 sulfatado como catalisador - Francisco, Thais Helena [UNIFESP] (2017)
The production of biodiesel generally occurs by means of a transesterification reaction of a vegetable oil or animal fat, in the presence of a catalyst and a short alcohol such as methanol or ethanol. In this project, the reaction of transesterification with the use of castor oil and methyl alcohol was investigated by varying the proportions between the reactants and the catalyst, the temperature and the reaction time. The best results obtained from conversion to methyl esters were in the proportions in moles of 1: 0.3: 18 for oil: catalyst: methyl alcohol, at the temperature of 140 oC, and in the reaction time of at least 2 h, reaching one of the samples 100 % yield. The heterogeneous catalyst used for the transesterification reactions, sulfated titanium oxide (SO42-/TiO2), has acidic characteristics and was synthesized by the sol-gel method. Castor oil is a promising vegetable oil, mainly in Brazil, to obtain biofuels, but it has very high viscosity due to the high content of ricinoleic acid in its composition, and this physical characteristic has been a negative factor for its applicability as a fuel, since high viscosity decreases the ability to boil, causing damage to the diesel engine. The transesterification reaction with castor oil yields carboxylic esters that are less viscous than the triglycerides of this oil, but the desiccated castor oil was applied to the biofuel synthesis in the transesterification reaction, in order to further decrease the viscosity of the final product. The use of dehydrated castor oil in the more optimized transesterification reaction resulted in the lowest viscosity obtained among all products, of 8.1 cSt. A chemical reaction that decreases the viscosity of castor oil is the dehydration reaction. It is a modification of the chemical structure of ricinoleic acid, with the elimination of the hydroxyl group (-OH) from its carbonic chain. To perform this procedure the dehydrating agent, potassium hydrogensulphate (KHSO4), was used under different reaction conditions, in a simple distillation system under reduced pressure and in a microwave reactor. The sol-gel method used for the synthesis of SO42-/TiO2 is a chemical procedure by which little operational energy was used and allowed to obtain a material with a high acidity, high surface area and homogeneous properties.